Aligning efficiency benchmarking with sustainable outcomes in the United Kingdom water sector. (1st June 2021) - Walker, Nathan L.; Styles, David; Gallagher, John; Prysor Williams, A.
Abstract: The provision of fundamental services by water and sewage companies (WaSCs) requires substantial energy and material inputs. A sustainability assessment of these companies requires a holistic evaluation of both performance and efficiency. The Hicks-Moorsteen productivity index was applied to 12 WaSCs in the United Kingdom (UK) over a 6-year period to benchmark their sustainability, based on eight approaches using different input and output variables for efficiency assessment. The choice of variables had a major influence on the ranking and perceived operational efficiency among WaSCs. Capital expenditure (utilised as part of total expenditure) for example, is an important input for tracking company operations however, potential associated efficiency benefits can lag investment, leading to apparent poor short-term performance following capital expenditure. Furthermore, water supplied and wastewater treated was deemed an unconstructive output from a sustainability perspective since it contradicts efforts to improve sustainability through reduced leakage and consumption per capita. Customer satisfaction and water quality measures are potential suitable alternatives. Despite these limitations, total expenditure and water supplied and wastewater treated were used alongside customer satisfaction and self-generated renewable energy for a holistic sustainability assessment within a small sample. They indicated the UK water sector has improved in productivity by 1.8% on average for 2014–18 and still had room for improvement, as a technical decline was evident for both the best and worst performers. Collectively the sample's production frontier was unchanged but on average companies moved 2.1% closer to it, and further decomposition of productivity revealed this was due to improvements in economies of scale and scope. Careful selection of appropriate input and output variables for efficiency benchmarking across water companies is critical to align with sustainability objectives and to target future investment and regulation within the water sector. Highlights: Choice of variable had major influence on company ranking. Capital expenditure as an input can lag efficiency results. Water supplied and treated unconstructive as an output. UK water sector improved in productivity by 1.8% on average (2014–18). UK water sector can still improve through technical advancements.